Use of Autologous Plasma as a Hair Follicle Holding Solution with Clinical and Histological Study - DR. Seema Garg, Dr. Anil Kumar Garg (International Journal of Innovative Research in Medical Science, 2017)
Background - One of the crucial aspects of hair transplant procedure is graft holding solution. We need a media which have same osmolality as of grafts cells, prevent acidosis, provides energy and prevent release of free radicals Aims and Objective - To evaluate plasma as a graft holding solution and its efficacy in terms of hair growth and graft survival. Material and Method - Equal number of Hair follicles were divided in two groups. Test group grafts were kept in freshly prepared autologous plasma, while the control group grafts were kept in ringer lactate. Under same conditions both group grafts were implanted male patients on right and left frontotemporal region in same density. Results were analysed on patients global photographs, tricoscan for hair density and thickness. The grafts were also send for histology by MTT stain to see viable cells in follicles. Results - on all parameters the results in plasma as graft holding solution were much better as compare to ringer lactate. Conclusion -As per our study the freshly prepared autologous plasma is a better graft holding solution as compare to ringer lactate in terms of cells viability, clinical results of early hair growth, decrease in anagen effluvium, and better quality of hair. Conflict of Interest -The authors have no conflict of interest and study self-funded.